2018
DOI: 10.21873/invivo.11308
|View full text |Cite
|
Sign up to set email alerts
|

Laminarin Promotes Immune Responses and Normalizes Glutamic Oxaloacetic Transaminase and Glutamic Pyruvic Transaminase Levels in Leukemic Mice In Vivo

Abstract: Laminarin did not affect animal appearances, but increased the body weight at all doses. It reduced the weight of liver at 2.5 and 5 mg/ml and of spleen at 5 mg/ml. Laminarin increased CD3 (2.5 mg/ml) and CD19 (1 and 5 mg/ml) cell populations but reduced CD11b (5 mg/ml) cell populations, however, these did not affect Mac-3 marker level. Laminarin at 1 mg/ml increased phagocytosis by macrophages from peripheral blood mononuclear cell, but did not affect those from the peritoneal cavity. Laminarin increased NK c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…Recent years have witnessed increasing attention of many plants due to their wide range of biological activities. Polysaccharides from Laminaria japonica have also been shown to possess a variety of biological functions, including antioxidation, antivirus, and tumor growth inhibition [4][5][6][7][8][9][10][11][12][13][14]. Therefore, we studied the human non-small-cell lung cancer A549 cells and discussed the effects of Laminaria japonica polysaccharides on its growth in vivo and vitro and its possible mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years have witnessed increasing attention of many plants due to their wide range of biological activities. Polysaccharides from Laminaria japonica have also been shown to possess a variety of biological functions, including antioxidation, antivirus, and tumor growth inhibition [4][5][6][7][8][9][10][11][12][13][14]. Therefore, we studied the human non-small-cell lung cancer A549 cells and discussed the effects of Laminaria japonica polysaccharides on its growth in vivo and vitro and its possible mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that Laminaria japonica polysaccharides have a variety of biological activities, including promoting fertility [4], alleviating metabolic syndrome [5], preventing vascular calcification [6], resisting virus [7,8], immunoregulating [9], and antioxidating [10]. In addition, Laminaria japonica polysaccharides have inhibitory effect on a variety of tumor cells, such as liver cancer cells, nasopharyngeal carcinoma cells, cervical cancer cells, and leukemia cells [11][12][13][14], but there are no reports on the effect of Laminaria japonica polysaccharides on human non-small-cell lung cancer A549 cells. In this study, we investigated the effects of Laminaria japonica polysaccharides on the survival of A549 cells in vitro and in vivo and its possible mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Murine myelomonocytic leukemia cells (WEHI-3 cells) and YAC-1 were obtained from the Food Industry Research and Development Institute (Hsinchu, Taiwan, R.O.C.). About 1×10 6 cells/ml in IMDM or RPMI-1640 medium supplemented with 10% fetal bovine serum, 100 units/ml penicillin, 100 μg/ml streptomycin and 2 mM L-glutamine were placed in 75 cm 2 tissue culture flasks under humidified 5% CO 2 at 37˚C as previously described (25).…”
Section: Methodsmentioning
confidence: 99%
“…The animal study project was reviewed and approved by the Institutional Animal Care and Use Committee of China Medical University (approval ID: 2017-009-1). In vivo experiments were carried out in accordance with the institutional animal ethical guidelines of the China Medical University as described previously (25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation